Examining the Value of Gratitude in Determining Selling Prices - Riyanti; Sofyan Syamsuddin; Darwis Said; Syarifuddin (LP2M IAIN Palopo, 2025)
This study attempts to explore and uncover the meaning of determining the selling price of fish traders.This study uses phenomenology as a method with data collection through interviews and documentation. The study shows that fish traders tend to ignore the calculation of the Cost of Goods Sold (COGS). The values ​​of gratitude and love expressed in the COGS are used as the basis for determining the selling price of fish. The low selling price of fish for informants is conceptualized as a